Pattern of congenital hand anomalies at a tertiary plastic surgery service in south-western Nigeria: a 10-year, cross-sectional retrospective review (2020)
Context: Although congenital hand anomalies are among the more common musculoskeletal anomalies worldwide, we do not know its prevalence in our practice. Aims: The aim of the study was to determine the pattern of congenital hand anomalies presenting to our tertiary plastic surgery outpatient service in South-Western Nigeria. Materials and Methods: This is a cross-sectional retrospective analysis of outpatient cases of congenital hand anomalies presenting over a 10-year period. Descriptive and inferential statistics were performed using frequencies, Student’s t-test and Chi-square as appropriate. The data were analysed using IBM SPSS Statistics 23.0. The statistical significance value was set at P < 0.05. Results: One hundred and twenty-two cases were identified. The highest number of cases was seen in the year 2012, 23 patients (19.3%). There was a male preponderance of 66 patients (55.1%). Thirty-two patients (26.2%) presented as neonates and 36 (29.5%) as infants. Bilateral anomalies were seen in 67 patients (54.9%). The most common anomaly was failure of differentiation, 88 patients (72.1%) followed by duplication, 26 patients (21.3%). Syndactyly with 43 patients (35.2%) was the most common anomaly under failure of differentiation. No significant associations were found between the type of anomaly and gender or laterality. Conclusions: Syndactyly was the most common congenital hand anomaly in this study. There was a preponderance of bilateral involvement in both syndactyly and polydactyly.